USM WELCOMES THE IMPLEMENTATION OF PPPM PT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUALA LUMPUR, 7 April 2015 The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato' Dr. Omar Osman welcomed the implementation of the new education blueprint or Pelan Pembangunan Pendidikan Malaysia (Pendidikan Tingg) (PPPM PT) which was launched today by Malaysian Prime Minister Dato' Sri Mohd. Najib Tun Abdul Razak.